Optimization design and rock‐breaking characteristics analysis of a self‐propelled swirling multi‐jet bit. Issue 6 (22nd October 2018) - Bi, Gang; Li, Mengmeng; Dou, Liangbin; Qu, Zhan; Zhao, Kai
Abstract: High rock‐breaking efficiency with limited discharge rate and increasing the extension capacity of the radial horizontal hole as far as possible are the key of the novel radial horizontal drilling technology. The performance of jet bit is the primary problem to be solved in this key technology. Based on multijet bit, a self‐propelled swirling jet bit was developed, and the design method was also presented. By conducting rock‐breaking experiments, the type and structural parameters of the self‐propelled swirling jet bit were optimized. The results demonstrate that when the jet pressure and standoff distance are constant, the rock‐breaking efficiency of self‐propelled combined swirling and round multijet bit is better than that of a self‐propelled swirling multijet bit. The combined swirling and round multijet bit with 1 + 4 holes is optimal. Since many structural parameters influence the rock‐breaking efficiency of the self‐propelled swirling jet bit, the optimal values for the structural parameters can be determined by adjusting the rock‐breaking capacity and drilling performance with different structural parameters. The proposed novel jet bit improves the speed of radial horizontal drilling significantly. Abstract : The radial horizontal drilling is a significant technology in exploration of low‐permeability and coal‐bed gas reservoir. The rock‐breaking efficiency of self‐propelled combined swirling and round multijet bit is better than self‐propelled swirling multijet bit. The combined swirling and round multijet bit with 1 + 4 holes is optimal.